TEC and Scintillation Study of Equatorial Ionosphere: A Month Campaign over Sipitang and Parit Raja Stations, Malaysia - Abdullah, M; Zain, A.F.M; Ho, Yih Hwa; Sabirin Abdullah, Sabirin (Science Publications, 2009)
Problem Statement: Ionospheric scintillations, which cause significant effects on satellite signals for communication and navigation, often takes place in equatorial region such as Malaysia. However, this disturbance are not fully understand due to few studies performed. This research reports the study and monitoring activity on Total Electron Content (TEC) and ionospheric scintillation in Malaysia using GPS measurements. Approach: One dual-frequency GPS receiver was positioned at the main station in Parit Raja, West Malaysia (1.86° N, 103.8° E) and Sipitang, East Malaysia (5.10° N, 115.56° E) respectively. Dual-frequency GPS data collected during the one-month ionospheric experimental campaign was used for TEC and scintillation computation and analysis. The TEC with 15 sec interval were computed from combined L1 and L2 code-pseudorange and carrier phase measurements. Whereas, the scintillation parameter S4 index was computed as a standard deviation of the received signal power normalized to average signal power every 60 sec on L1. A corrected S4 (without noise effects) was also computed and used in the analysis. Results: It was found that the daily maxima vTEC for Parit Raja (PR) ranged from 38-100 TECU, which is generally higher than those of Sipitang, which ranged from 30-42 TECU. However, a general consistency for both stations can be seen during the 1 month campaign period. Conclusions/Recommendations: In conclusion, these results show good agreement in the existence of the equatorial anomaly observed during moderate solar flux conditions and undisturbed geomagnetic condition. This will contributes to the knowledge of equatorial ionosphere and help in space weather condition. However, to better understand and characterize the ionosphere over Malaysia, more campaigns should be encouraged.